Profile Of Animal Bite Cases Attending Urban Health Centers in Surat City: A Cross-Sectional Study - Umarigar, Pradeep; Parmar, Gaurang; Patel, Prakash B; Bansal, R K (National Journal of Community Medicine, 2012)
Context: Exposure to dog bites is an important public health problem, these bites not only cause increase morbidity and mortality but also loss of work days and cost for treatment. Moreover, myths and practices amongst people prevent appropriate post exposure treatment. Objectives: The survey was conducted with objectives to study the epidemiological characteristics of victims of animal bite injuries and health seeking behaviour of persons with animal bite. Methodology: It was a cross-sectional study conducted among new cases of animal bites registered at Urban Health Centres of Surat city. Results: Out of total 337 cases of animal bites majority (48%) belongs to 15-45 years of age-group and 79 % were male. Ninety four percent of cases were bitten by stray dog. Children less than 15 years of age were more likely to provoke a bite (P< 0.05).Category II bites were seen in 198(59 %) of cases. In 89.8% cases lower extremities were affected. Only two hundred forty cases had attended the ARV clinic within 24 hours of bite. Only 65 % of cases had done the wound washing. Conclusion: Local treatment of the wound soon after a bite is an important step in the management of a case and this was lacking in most of the subjects. Efforts to eliminate the stray dogs are required.